Early‐life dietary and epigenetic influences on childhood musculoskeletal health: Update on the UK component of the ALPHABET project. Issue 2 (8th May 2018) - Curtis, E. M.; Suderman, M.; Phillips, C. M.; Relton, C.; Harvey, N. C.
Abstract: The ALPHABET project, funded through the European Research Area Healthy Diet for a Healthy Life Biomarkers call, aims to expand the knowledge base regarding interactions between diet, epigenetics and offspring health, characterising biomarkers that may inform future health strategies. This review focuses on the UK Biotechnology and Biological Sciences Research Council (BBSRC)‐funded component in which the aim was to (1) generate and collate early‐life epigenetic data and (2) investigate early diet and epigenetic marks as predictors of later bone health. The project builds on a wealth of evidence implicating environmental factors, such as maternal diet and body composition, as influences on the long‐term health and development of the offspring, and that these relationships might be mediated at least in part through epigenetic signals. Experimental studies in animal models have demonstrated that manipulation of maternal diet during pregnancy leads to altered offspring epigenetic marking and phenotype. Human studies convincingly demonstrate associations between early environment and later health and disease for outcomes across musculoskeletal, respiratory, neurodevelopmental and cardiometabolic health. The priority now is to find ways in which such observations can be translated into improved lifelong health. A key approach is to identify early biomarkers of adverse health outcomes and then to test these, and subsequent interventions, in trials aimed at identifying strategies to optimise health throughout the life course. The ALPHABET project will inform this process for musculoskeletal outcomes, and the project as a whole should help elucidate not only novel mechanisms, but also potential strategies to reduce the burden of musculoskeletal, respiratory, neurodevelopmental and cardiometabolic disease in future generations.